Staff and students of the West Coast School of Nature Study - French, Gerald L. (photographer):::Creator::::::::::::
Negative shows a group portrait of the staff and students of the West Coast School of Nature Study. They are standing in front of a group of buildings. The sign on one building reads: "Death Vall[ey] New Hotel."